Effects of Initial Performance, Gross Efficiency and O2peak Characteristics on Subsequent Adaptations to Endurance Training in Competitive Cyclists - Skovereng, Knut; Sylta, Øystein; Tønnessen, Espen; Hammarström, Daniel; Danielsen, Jørgen; Seiler, Stephen; Rønnestad, Bent R.; Sandbakk, Øyvind (Frontiers in Physiology, 2018)
The present study investigated the effects of initial levels of cycling performance, peak oxygen uptake (VO2peak) and gross efficiency (GE) on the subsequent adaptations of these variables and their relationship following high-intensity training designed to increase VO2peak in competitive cyclists. Sixty cyclists (VO2peak = 61±6 mL.kg-1.min-1) were assigned a twelve-week training program consisting of twenty-four supervised high-intensity training sessions and ad-libitum low intensity training. GE was calculated at 125, 175 and 225 W and performance was determined by mean power during a 40-minute time-trial (Power40min). In addition to correlation analyses between initial level and pre- to post-intervention changes of the different variables, we compared these changes between four groups where participants were categorized with either low and/or high initial levels of VO2peak and GE. Average volume of high- and low-intensity training during the 12-week intervention was 1.5 ± 0.3 and 8.3 ± 2.7 and hours.wk-1 respectively. Following the 12-week training period, there was a significant increase in absolute and body mass normalized VO2peak and Power40min (p < 0.05) and a significant decrease in GE (p < 0.05) for all athletes pooled. There was no change in body mass following the 12-week training period. We found a moderate negative correlation between initial level of VO2peak and the change in VO2peak following the training period (r = -0.32; p < 0.05). A small negative correlation was also found between initial Power40min and its change following training both when expressed in absolute power and power normalized for body mass (r = -0.27 and -0.28; both p < 0.05). A moderate negative correlation was also found between initial levels for GE and its change following training (r = -0.44; p < 0.01). There were no differences between the four groups based on initial VO2peak and GE in the response to training on VO2peak, GE or Power40min (all p > 0.12). In conclusion, the present findings suggest that there are statistically significant effects of initial levels of cycling performance and VO2peak and on the subsequent adaptations following a 12-week high-intensity training program, but the small and moderate effects indicate limited influence on training practice.